Characterization of the unarmored dinoflagellate Pseliodinium pirum (Ceratoperidiniaceae) from Jiaozhou Bay, China. Issue 1 (28th May 2019) - Hu, Zhangxi; Deng, Yunyan; Luo, Zhaohe; Shang, Lixia; Kong, Fanzhou; Gu, Haifeng; Zhao, Zengxia; Tang, Ying Zhong
SUMMARY: A strain of Pseliodinium pirum was isolated from Jiaozhou Bay, China, identified based on a recently emended classification, and further characterized for its morphology using light, scanning electron, and transmission electron microscopy, and phylogeny based on SSU and partial LSU rDNA sequences. The pigment composition, life history, and potential effects on aquatic animals were also examined. We observed the typical characteristics of Ceratoperidiniaceae, in which its apical structure complex (ASC) formed a circular loop, and the ASC of our isolate comprised four to five rows of vesicles, and connected with sulcal intrusion. Epifluorescence and transmission electron microscopy revealed a bean‐shaped, centrally located nucleus, with at least 76 chromosomes. Numerous rod‐shaped chloroplasts were in connection to the irregularly shaped pyrenoids. Pigment analysis showed that peridinin was the most abundant among all carotenoids and other pigments. Phylogenetic analyses using maximum likelihood and Bayesian inference indicated that our isolate is conspecific with the entity Cochlodinium cf . helix (accession No. KF245459), but different from Ceratoperidinium, Kirithra, and other unidentified species of the family Ceratoperidiniaceae. Pseliodinium pirum could produce sexual, thin‐walled cyst, with subspherical and spherical shape and smooth surface (without spines or rough projections). The cyst could germinate within 3 days. Bioassays did not show adverse effects of P. pirum on the finfish Oryzias melastigma and the rotifer Brachionus plicatilis, indicating it may not be a harmful species.